Pengaruh Lingkungan Kerja Fisik Dan Loyalitas Kerja Terhadap Retensi Karyawan Di PT Masshima Jaya Makmur Tangerang - Detri Atun Hasanah; Melda Wiguna (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of physical work environment and job loyalty on employee retention at PT Masshima Jaya Makmur Tangerang. The study used a quantitative method with an associative approach and a saturated sample technique on all 57 employees. Data were collected through questionnaires and analyzed using simple linear regression, multiple linear regression, and Pearson correlation test with the help of SPSS version 26. The results showed that the physical work environment had a positive and significant effect on employee retention with a regression coefficient of 0.740 and a significance value of 0.000 < 0.05, and had a strong relationship with a correlation coefficient of 0.756. Job loyalty also had a positive and significant effect on employee retention with a regression coefficient of 0.796 and a significance value of 0.000 < 0.05. Simultaneously, the physical work environment and work loyalty had a positive and significant effect on employee retention with the regression equation Y = 4.398 + 0.345 X1 + 0.508 X2, where job loyalty was a more dominant variable in influencing employee retention